DOPRINOS DRAGUTINA KNIEWALDA UVOĐENJU ŽIVOGA NARODNOG JEZIKA U BOGOSLUŽJE RIMOKATOLIČKE CRKVE NA DRUGOME VATIKANSKOM KONCILU. - MRKONJIĆ, Tomislav; VLAHEK, Zlatko (Slovo (05836255), 2024)
The introduction of the vernacular into liturgy is a centuries-old issue that has repeatedly arisen in response to the challenges of historical events; it has triggered debate at both the national and international level. The liturgical reform movement reached a significant turning point with the introduction of the vernacular into liturgy. This change enabled the faithful to actively participate in liturgy in an understandable way and introduced them to the celebration of the mysteries of Christ. The pioneer of the liturgical movement in Croatia was Dr. Dragutin Kniewald. His efforts and research in uncovering the heritage of Old Church Slavonic liturgical sources played a decisive role in the introduction of the vernacular into liturgy, especially as the use of Latin continued to decline. Kniewald is not only a recognised and esteemed scientist in Croatia, but has also established himself internationally. When he was invited to take part in the Preparatory Commission for the Second Vatican Council, he made an important contribution by informing the members of the commission about the heritage of Old Church Slavonic liturgy in Croatia, thus effectively promoting the usefulness and value of introducing the vernacular into liturgy. He did not abandon these efforts even when the motu proprio Veterum sapientia, a document offering guidelines for preserving the Latin language during the time of the Council, was published. Kniewald continued to address the commission members, emphasising the importance of celebrating the Holy Mysteries in one's native tongue. He presented Glagolitic liturgical books in Old Church Slavonic to the assembly and received great acclaim, as evidenced by newly discovered materials from the Vatican Apostolic Archives, which have been used for the first time in this research. Through his expertise and contributions, Kniewald helped prepare the debate speeches of the Croatian bishops during the Council, thus spreading knowledge of Old Church Slavonic liturgy at an international level. All this affirms that Kniewald was indeed a true leader in the liturgical renewal in Croatia, and that his contribution and active support strongly influenced the introduction of the vernacular in liturgy during the Second Vatican Council.